Comparing the enhanced sensing interfaces of differently oriented carbon nanotubes onto silicon for bio-chip applications - Taurino, I.; Carrara, S.; Giorcelli, M.; Tagliaferro, A.; De Micheli, G. (2011 4th IEEE International Workshop on Advances in Sensors and Interfaces, 2011)
Carbon nanotubes improve the sensitivity of electrochemical biochips. An optimized integration of the nano/bio/CMOS interface is required to realize accurate and low-cost sensors for applications in personalized medicine. The nanotubes orientation on the chip is a key parameter. The role of the sidewalls and the tips surface on the electro-activity of the nano-sensor is still subject of debate in the literature. In this paper, a comparison between vertical densely-packed and randomly-oriented carbon nanotubes directly growth on silicon wafer is proposed in order to identify the best nano-system for biosensing purposes. The comparison is done by using contact-angle measurements, energy dispersive X-ray analysis and electrochemical voltammetry.